Conserved action of β‐catenin during female fate determination in the red‐eared slider turtle. Issue 2 (4th March 2013) - Mork, Lindsey; Capel, Blanche
SUMMARY In reptiles such as the red‐eared slider turtle Trachemys scripta, development of an ovary from the bipotential gonad requires a coordinated expansion of the cortical domain and regression of the medulla. While estrogen, which is necessary and sufficient for ovarian development in non‐mammalian vertebrates, is thought to feminize both compartments, it remains unclear whether there is a signaling relationship between the two domains that coordinates their fates. We show that aromatase, the estrogen‐synthesizing enzyme, is localized to the medulla of the differentiating turtle ovary and that differentiation of the medulla precedes and is independent of cortical expansion. Coordinated feminization of the two domains may therefore rely on an estrogenic signal from the differentiating medulla. In eutherian mammals, where estrogen is dispensable for early ovary development, the canonical Wnt signaling pathway is critical for female fate determination. Whether this function is conserved among vertebrates and how it is potentially integrated with estrogen signaling are uncertain. Using a novel in vitro turtle gonad culture system, we demonstrate that ectopic activation of the canonical Wnt signaling pathway in presumptive male gonads induced a partial sex‐reversal of the medulla, but inhibition of the pathway was not sufficient to sex‐reverse differentiating ovaries. These patterns are similar to those previously observed in mice. Wnt signaling appears to function downstream of estrogen, as ectopic activation of the pathway rescued female development when estrogen synthesis was inhibited. Our findings therefore suggest that the ovary‐promoting effects of the Wnt signaling pathway may be functionally conserved between mammals and reptiles.